Gambaran Efikasi Diri Maternal pada Ibu Remaja di Wilayah Kerja Puskesmas Sukowono Jember - Martina Fitria; Dini Kurniawati; Perdani Juliningrum (Pustaka Kesehatan, 2021)
Adolescent mothers are women with a transition period between childhood and adulthood but must act as parents. Adolescent mothers have limited experience in caring for babies, thus often feeling incompetent and not confident. Maternal self-efficacy is self-confidence in the ability, a mother's competence perceived in caring for her baby, and perceptions of the role of mother. Confidence is a factor that influences the adaptation and achievement of a mother's identity in baby care and the closeness of mother to child. This study aimed to determine the description of maternal self-efficacy of adolescent mothers at the Public Health Centre Sukowono Jember Regency. This research used method analytic descriptive and total sampling methods with 50 adolescent mothers as respondents. Data were analyzed by univariate analysis. These results showed that more than half of the total respondents had low maternal self-efficacy (54%). Low maternal self-efficacy will delay the transition of the mother's role and limit the satisfaction in achieving the mother's role. Therefore, Nurses are important to pay more attention to adolescent mothers in pre-pregnancy services to improve their ability and increase their readiness and skills to carry out their roles as new mothers.